Community Service Activities on Developing Instant holat Spice Products for Housewife Groups in Medan Johor and Medan Tuntungan, Medan City - Wahyu Haryati Maser; Emma Marsella; Ajuan Ritonga; Mangaraja Halongonan Harahap (Journal of Saintech Transfer, 2026)
This community service aimed to assist housewife groups in Medan Johor and Medan Tuntungan, Medan City, in developing instant holat spice products. Holat, a traditional Mandailing dish, holds cultural significance but is time-intensive and difficult to prepare, as well as the raw materials are difficult to find in urban areas. The initiative sought to preserve local culinary traditions while providing an economic opportunity for the target group. Activities included training sessions on ingredient selection, production techniques, food safety, packaging, and marketing strategies. Through these efforts, participants gained skills to produce instant holat spices and market them effectively. The program successfully empowered the participants by fostering entrepreneurship and promoting traditional cuisine spices in a modern way, contributing to both cultural preservation and economic improvement.